Building Safety System Using LASER Sensors (مجلة المنصور, 2022)
Safety system is a device or number of devices and tools in integral way to guarantee the protection of the target building, car, office, etc. In this paper we propose the design of safety system that can be controlled by the computer by using the keyboard and the connection point between the computer and the safety system is the parallel ports of the computer (LPT1). This system is built to save the home or office or building (the system is developed as the size and importance of the building ) where the building saved by using the lasers and that are connected with the sensors to guarantee that no one can enter the building without permission then thesystem will record that penetration and its time and take a photo to the person who entered and make the alarm working and calling the user or the security administrator of the building, this system is designed in two parts the physical part(hardware) and the programming part (software).